The Influence Of Business Capital and Family Support On Entrepreneurial Interest In Economics Education Students Class Of 2019-2022, University Of Jambi - Agum Agum Yudha Joni; Siti Syuhada; Romi Kurniadi (Jurnal Smart: Sosial Ekonomi Kerakyatan, 2023)
This study aims to determine the effect of business capital and family support on entrepreneurial interest in economic education students in the 2019-2022 batch of Jambi University both partially and simultaneously. This research is research with a quantitative approach. The population in this study was 119 Economic Education Students from the Class of 2019-2020 at Jambi University. Data collection technique by distributing questionnaires via Google Forms. The data analysis technique used is multiple linear regression analysis with the SPPS SPSS 21.0 for Windows assistance program. The results of this research indicate that the use of the Google site partially influences learning achievement as evidenced by the obtained value of t_(calculation) > t_(table) namely 3.012 > 1.658 and a significance value of <0.05, namely 0.003 < 0.05. The learning motivation variable partially influences learning achievement as evidenced by the value of t_(count) > t_(table) namely 3.064 > 1.658 and the significance value < 0.003, namely 0.003 < 0.05. And simultaneously it also has an effect where the value of 〖F〗_(calculation) is greater than 〖F〗_(table) namely 10.609 > 3.1 and the significance value < 0.05, namely 0.000 < 0.05. So H_(a) is rejected and H_0 is rejected, so that there is a significant influence between the use of the Google Site and Learning Motivation on the Learning Achievement of Economics Education Students Class of 2019-2020, Jambi University.